Morphology of large ZSM-5 crystals unraveled by fluorescence microscopy - Roeffaers, Maarten B. J.; Ameloot, Rob; Baruah, Mukulesh; Uji-i, Hiroshi; Bulut, Metin; De Cremer, Gert; Mueller, Ulrich; Jacobs, Pierre A.; Hofkens, Johan; Sels, Bert F.; De Vos, Dirk E. (Journal of the American Chemical Society, 2008)
Understanding the internal structure of ZSM-5 crystallites is essential for improving catalyst performance. In this work, a combination of fluorescence microscopy, AFM, SEM, and optical observations is employed to study intergrowth phenomena and pore accessibility in a set of five ZSM-5 samples with different crystal morphologies. An amine-functionalized perylene dye is used to probe acid sites on the external crystal surface, while DAMPI (4-(4-diethylaminostyryl)-N-methylpyridinium iodide) is used to map access to the straight channels in MFI from the outer surface. The use of these dyes is validated by studying the well-understood rounded-boat type ZSM-5 crystals. Next coffin-shaped ZSM-5 crystals are considered; we critically evaluate the seemingly conflicting 2-component and 3-component models that have been proposed to account for the hourglass structure in these crystals. The data prove that observation of an hourglass structure is essentially unrelated to a 901 rotation of the pyramidal crystal components under the (010) face. Hence, in perfectly formed coffin-shaped crystals, the straight channels can be accessed from (010). However, in other crystal batches, sections with a 90 degrees rotation can be found; they are indeed located inside the crystal sections under (010) but often only partially occupy these pyramidal components. In such a case, both straight and sinusoidal pores surface at the hexagonal face. The results largely support the 3-component model, but with the added notion that 900 rotated sections (as proposed in the 2-component model) are most likely to be formed inside the defect-rich, pyramidal crystal sections under the (010) faces.